Penindakan Genosida terhadap Etnis Kurdi di Irak: Perspektif Hukum Pidana International dan Hukum Pidana Islam - Kukuh Satrya Perdana; Aris Widodo (IAIN Langsa, 2026)
This study aims to analyze the juridical qualification of the genocide against the Kurdish ethnic group in Iraq from the perspective of International Criminal Law, examine the concept of criminal responsibility for genocide within Islamic Criminal Law, and formulate a model for prosecuting genocide perpetrators through the integration of these two legal systems. This research employs a qualitative library research method with a normative legal approach. Primary sources include the Convention on the Prevention and Punishment of the Crime of Genocide (1948), the Rome Statute (1998), the Qur’an, Hadith, and other relevant legal literature. The data were analyzed using content analysis and comparative analysis methods. The findings reveal that the actions of Saddam Hussein’s regime against the Kurdish population through the Anfal Campaign and the Halabja chemical attack fulfill the legal elements of genocide under International Criminal Law, particularly the requirements of actus reus and dolus specialis. From the perspective of Islamic Criminal Law, these acts constitute a grave jarimah that violates the principles of hifz al-nafs, al-'adl, the prohibition of zulm, and the objectives of maqasid al-shari'ah.